Volatile anesthetic sevoflurane pretreatment alleviates hypoxia‐induced potentiation of excitatory inputs to striatal medium spiny neurons of mice. (6th August 2019) - Fukuda, Masataka; Ando, Nozomi; Sugasawa, Yusuke; Inoue, Ritsuko; Nakauchi, Sakura; Miura, Masami; Nishimura, Kinya
Abstract: Sevoflurane, a commonly used anesthetic in surgery, has drawn attention because of its preconditioning effects in hypoxic conditions. To investigate the preconditioning effects in the striatum, a common site for ischemic stroke, we collected whole‐cell current‐clamp recordings from striatal medium spiny neurons. In our in vitro brain slice experiments, deprivation of oxygen and glucose depolarized the striatal neurons to subthreshold potentials, and the pre‐administration of sevoflurane (4%, 15 min) prolonged the time to depolarization. Furthermore, transient hypoxia induced the potentiation of excitatory postsynaptic potentials, which play a part in post‐ischemic excitotoxicity. Glibenclamide, a KATP channel inhibitor, reversed the prolonged time to depolarization and the prevention of the pathological potentiation of excitatory responses, indicating that the short exposure to sevoflurane likely participates in neuroprotection against hypoxia via activation of KATP channels. A monocarboxylate transporter blocker, 4‐CIN, also depolarized striatal neurons. Interestingly, the blockade of monocarboxylate transporters that supply lactate to neurons caused the pathological potentiation, even in the presence of enough oxygen and glucose. In this case, sevoflurane could not prevent the pathological potentiation, suggesting the involvement of monocarboxylate transporters in the sevoflurane‐mediated effects. These results indicate that sevoflurane protects striatal neurons from hypoxic damage and alleviates the pathological potentiation. Under these conditions, sevoflurane may become an effective intervention for patients undergoing surgery. Abstract : In striatal slice experiments, pre‐administration of the volatile anesthetic sevoflurane ameliorated hypoxia‐induced membrane depolarization and EPSP potentiation via activation of KATP channels. Membrane depolarization and EPSP potentiation were also induced by the monocarboxylate transporter blocker 4‐CIN. Interestingly, 4‐CIN removed the effects of sevoflurane on energy restriction, suggesting the involvement of lactate transport in the neuroprotective effects of sevoflurane.